Editorial: Relaunching Cultural Science. Issue 1 (10th July 2018) - Hartley, John
Cultural Science Journal is delighted to announce our successful migration to the Ubiquity Press platform. We are now ready to publish submissions received during 2018, which will comprise Volume 10 of the journal. We begin with several papers on the theme of 'open knowledge' and will add new papers on all topics as they are accepted. Each volume of the relaunched Cultural Science Journal will be cumulative over the year, so that work will be published in a timely manner once it is reviewed, revised and accepted, without having to wait for an issue. We are planning for 12 articles per annum to begin with, and are also open to reviews and commentary as well as research. Initially, the costs of publishing Open Access are borne by the Centre for Culture & Technology (CCAT) at Curtin University. In later volumes, we will encourage authors to seek funding from their own institutions to support publication of their articles. We hope to support the journal through events such as research workshops and conferences.